Observations on cucullanid nematodes from freshwater fishes in Mexico, including Dichelyne mexicanus sp. n - Caspeta-Mandujano, J M; Moravec, F; Salgado-Maldonado, G (Folia parasitologica, 1999)
A new cucullanid nematode, Dichelyne mexicanus sp. n., is described from the intestine of three species of fishes, Agonostomus monticola (Bancroft) (Mugilidae, Perciformes) (type host), Ictalurus balsanus (Jordan et Snyder) (Ictaluridae, Siluriformes) and Cichlasoma beani (Jordan) (Cichlidae, Perciformes), from three rivers (La Maquina River, Veracruz; Chontalcoatlán River, Guerrero and Santiago River, Nayarit) in central Mexico. This species is characterised by the absence of a ventral sucker in the male (subgenus Dichelyne) and it differs from its congeners mainly in possessing very unequal and dissimilar spicules (left 0.465-0.768 mm and right 293-548 mm long), an asymmetrical gubernaculum, and two intestinal caeca. Another cucullanid nematode, Cucullanus caballeroi Petter, 1977, is reported from Dormitator maculatus (Bloch) (Eleotridae, Perciformes) from the La Palma and La Maquina Rivers and Balzapote stream, Veracruz, being briefly described and illustrated; this represents a new host record. Findings of D. mexicanus and C. caballeroi represent a new record of cucullanid nematodes from fishes in Mexican fresh waters.
Keywords: Perciformes; Nematode Infections; Mexiko; Animals; Fresh Water; nemoci ryb; Nematoda; Female; nematodózy; zvířata; Ictaluridae; mužské pohlaví; hlístice; Fish Diseases; Male; sladká voda; Mexico; ženské pohlaví